Fluid evolution and petroleum accumulation in the precambrian gas reservoirs of the Sichuan Basin, SW China. (April 2023) - Huang, Yahao; Luo, Tao; Tao, Ze; He, Zhiliang; Tarantola, Alexandre; He, Sheng; Guo, Xiaowen; Zhang, Dianwei; Sun, Ziming
Abstract: Deep marine carbonates comprise one of the most significant reservoir types globally. Reconstruction of Precambrian oil reservoirs and the complex tectonism that affected Precambrian carbonate reservoirs demonstrate the complexity of the natural gas enrichment mechanism. A comparison between the fluid evolution of the well-preserved reservoirs in the central Sichuan Basin and the poorly preserved reservoirs in the southeastern Sichuan Basin offers insights into the factors that control the preservation of ancient reservoirs. We conducted geochemical analysis of the multistage cementation sequence, Raman quantitative analysis on fluid (gas) inclusions, and rare earth element (REE) analysis of diagenetic fluid environments. Hydrocarbon migration can cause variations in the diagenetic environment. Quantitative Raman measurements of the trapping pressure, trapping temperature, and composition of fluid (gas) inclusions are also useful in defining periods of gas accumulation. In situ U–Pb dating results of dolomite veins indicate that extensive dolomitization in the Sichuan Basin began during the early Cambrian. In the central Sichuan Basin, reservoir pressure evolved from normal during the Middle Jurassic to strongly overpressured during the mid-Cretaceous. Overpressure generated before Himalayan tectonism appears to be positively correlated with gas preservation. Overpressure within inclusions bearing hydrogen sulfide indicates that thermochemical sulfate reduction (TSR) does not produce intense dissolution that increases the porosity of carbonate reservoirs and reduces pore pressure. Poorly preserved reservoirs were intruded by exogenous and hydrothermal fluids but remained normally pressured. Secondary methane-rich gas inclusions record normal pressure conditions during the early Paleogene. Highlights: Sinian Dengying Formation has different diagenetic sequences under different preserved conditions. Source of vein precipitation evaluate the sealing ability of reservoirs. Raman quantitative analysis determines PVT-x properties of CH4 bearing inclusions. Paleo-pressure evolution indicates the gas accumulation mechanism.